Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Raymond L. Cummins, December 20, 1988 - Cummins, Raymond L.et al (1988)
Iowa Christmas bird counts of species found in Jamaica contributed by Raymond L. Cummins, December 20, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed